AN ANALYSIS ON THE EFFECT OF EMPLOYEE SATISFACTION IN BUSINESS ORGANIZATIONS - Soewarto, F. X.; Subyantoro, Arief (Archives of Business Research, 2020)
This research aims to study the effect of independent variables (Colleagues Support) on the dependent variable (Job Satisfaction) through one intervening variable (Discipline). The data analysis is path analysis using Partial Least Square (PLS) with single-mediator. The data processing uses software Warp PLS 5.0. The respondents in this research are all employees in three business organizations which are in the same neighborhood and have 61 neighbors. The results showed that there are influences of Colleague Support on Discipline, Colleague Support on Job Satisfaction, Discipline on Job Satisfaction, and Colleague Support on Job Satisfaction with Discipline as the intervening variable.